THE ERA OF METAMODERNISM AND ITS IMPACT ON THE MODEL OF INTERACTION OF AGRARIAN ENTERPRISES - G. N. Ryazanova (Вестник университета, 2020)
The period of the change of the era of postmodernism to metamodernism (metamodern) has been considered. The features of metamodernism, as the ambiguous orientation of philosophical and worldview concepts and its impact on the economic space of different levels of the hierarchy have been revealed. It has been emphasized, that the consequences of the metamodern era especially sharply reflected in the Russian economy of the 1990s, since the systemic ties that developed during the modern and postmodern periods were destroyed due to political transformations and the import of liberal institutions into the country’s economy. The level of a microeconomic agent on the example of enterprises in the agricultural sector has been reviewed. The stages of evolution of the development of agricultural enterprises have been identified. The transformation of the interaction model of agricultural enterprises with other microeconomic agents in the era of metamodernism has been traced.